Profil Penggunaan Insulin Pada Pasien Diabetes Melitus Tipe 2 Dengan Ulkus/ Gangren Di Rumah Sakit Umum Daerah (RSUD) Kabupaten Sidoarjo - Hariyati, Fera; Hasmono, Didik; Kasih, Elisabeth (Faculty of Pharmacy, Widya Mandala Surabaya Catholic University, Indonesia, 2018)
Diabetis mellitus is still a health problem in the world. It is a condition of hyperglycemia which is at risk of causing macrovascular and microvaskular complications. The prevalence of diabetes mellitus continues to increase throughout the world, including in Indonesia. One of diabetes complications is diabetic ulcer or gangrene. Diabetic ulcer or gangrene is common complication of diabetes mellitus wich can be caused by uncontrolled blood glucose levels. The aim of this study was to find the profile of insulin use in patiens with type 2 diabetes mellitus with ulcer or gangren in RSUD Kabupaten Sidoarjo. It was an observational-descriptive study. Data were collected retrospective using purposive sampling method in the period of January 2017 to December 2017 at RSUD Kabupaten Sidoarjo. The results of observational study on 19 patients showed the insulin therapy used in this study, where 42% of patients used single insulin therapy and 58% of patiens used combination insulin therapy. In this study the commonly used single insulin was rapid acting insulin (Novorapid®) 42%, whereas the combination insulin used was rapid acting insulin with long acting insulin (Novorapid®-Lantus®) 58%. Based on glycemic target, patients with blood glucose levels reached the glycemic target were 10% of patients, the ones that not reached the glycemic target were 80% of patients and the ones that reached hypoglicemia were 10% of patients. In this study, the severity category of diabetes mellitus patients with ulcers/ gangrene was gangrene 58%, ulcers 26%, cellulitis 11% and sepsis 5%.